Clinical inertia in hypertension: a new holistic and practical concept within the cardiovascular continuum and clinical care process. (4th July 2019) - Pallarés-Carratalá, Vicente; Bonig-Trigueros, Irene; Palazón-Bru, Antonio; Esteban-Giner, María José; Gil-Guillén, Vicente Francisco; Giner-Galvañ, Vicente
Abstract: Purpose: Recognition of clinical inertia is essential to improve the control of chronic diseases. Although it is very intuitive, a better interpretation of the concept of clinical inertia is lacking, likely due to its high complexity. Materials and Methods: After a review of the published articles, we propose a practical vision of inertia, contextualized within the clinical process of hypertension care. Results: This new vision enables the integration of previous terms and definitions of clinical inertia, as well as proposing specific strategies for its reduction. Conclusion: Although some concepts should be considered as 'justified inertia' or 'investigator inertia', the idea that inertia may be present throughout the continuum of care gives physicians a holistic view of the problem that is easily applicable to their clinical practice. Measures to overcome inertia are complicated because of the intrinsic complexity of the concept.